ELIMINATION OF TAX COMPLEXITY ISSUE THROUGH FINANCIAL LITERACY - Faud Bahramov (Revista de Studii Financiare, 2023)
Modern taxation systems often experience complexity and investigations have attempted to define whether the tax complexity has an impact on the compliance of taxpayers. A low level of literacy can be an obstacle in the tax system. This paper will examine the impact of financial literacy on tax revenues to prove the relationship between literacy and taxation. The study will also provide suggestions for developing financial literacy which may reduce the negative influence of tax complexity on tax compliance. The educational systems do not provide taxation as a subject at any stage, however, tax knowledge is required for understanding taxes and for implementation of tax calculations and those skills directly affect the finances of individuals and the performance of businesses. A low level of financial education and tax knowledge in society affects the financial attitude of individuals and households which can lead to lower tax compliance and eventually, create a fertile environment for tax evasion. The tax complexity concerns not only people and businesses but also governments and tax administrations, because it also decreases tax revenues in the end. The study will use a simple regression model as a method in order to find out the relationship between financial literacy and taxation, as well as it will support suggestions to eliminate tax complexity issues. The main tax variables will be taken from the Eurostat database and financial literacy variables will be sourced from the OECD survey of financial competencies. Every individual and country must take financial education into serious consideration to avoid the anticipated consequences in personal life and negative results in economic development.